Upaya Meningkatkan Hasil Belajar IPA dengan Menggunakan Model Pembelajaran Kooperatif Tipe Student Team Achievement Divisions (STAD) dan Numbered Heads Together (NHT) pada Peserta Didik Kelas IV SDN 1 Anjir Mambulau Timur: Efforts to Improve Science Learning Outcomes by Using Student Team Achievement Divisions (STAD) and Numbered Heads Together (NHT) Cooperative Learning Models in Class IV Students of SDN 1 Anjir Mambulau Timur - Hilda Indriyani; Ichyatul Afrom (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to (1) describe the increased activity of students in teaching and learning activities using the cooperative learning model of Student Team Achievement Division and Numbered Heads Together, (2) improve science learning outcomes for fourth grade students of SDN 1 Anjir Mambulau Timur after using the model cooperative learning type Student Team Achievement Division and Numbered Heads Together. The type of research used by researchers is Classroom Action Research (CAR) which tries to solve or answer the problems faced in the current situation. The subjects in this study were 15 students consisting of 3 men and 12 women. For data collection techniques used are observation and tests. While in this study using data analysis namely qualitative (obtained through observation) and quantitative (derived from the pretest and posttest). The results showed that: (1) the activities of students when using the cooperative learning model Student Team Achievement Division and Numbered Heads Together were seen to increase in the first cycle with an average of 3.5 and the second cycle with an average of 3.8 with good categories , (2) there is an increase in science learning outcomes through the use of cooperative learning models of Student Team Achievement Division and Numbered Heads Together which show the initial results of 40%, in the first cycle 86.6% and in the second cycle 100%.